MOLECULAR DYNAMIC SIMULATION OF REFLECTIVITY COEFFICIENT OF A DENSE SEMICLASSICAL PLASMA - Nigmetova, G.N.; Ramazanov, T.S.; Kosov, V.N.; Nurekenov, Kh.T. (Recent Contributions to Physics, 2008)
Molecular dynamic simulation results for reflectivity coefficient of a dense semiclassical plasma are presented on the basis of the microscopic functions described of electrodynamical state of the system.